Facile colorimetric detection of As(V) in Rice with immobilized acid phosphatase on hollow metal-organic frameworks hybrid with peroxidase-like activity - Zhiyang Qin; Zhuolan Xu; Yixin Liu; Xinguang Qin; Gang Liu; Xinlin Wei; Haizhi Zhang (Food Chemistry: X)
Quantitative analysis of As(V) in rice is of great significance for food safety and heavy metal pollution control. Here, a facile colorimetric method for As(V) detection was constructed by using immobilized acid phosphatase (ACP) in hollow metal-organic frameworks hybrid. Metalloporphyrin and gold nanoparticles modified hollow zeolite imidazole framework-8 [Au/HZIF-8@TCPP(Fe)], named AuHT, was chosen here as ACP immobilizing carrier with peroxidase-like activity. Firstly, the morphology, structure, immobilization efficiency and catalytic ability of obtained AuHT@ACP were fully characterized. Then, based on the inhibition of As(V) on immobilized ACP and cascade reaction mediated by ACP and AuHT, a colorimetric biosensor was established with excellent simplicity. After comprehensive validation, this colorimetric method presented the advantages of wide linear range (10.0–1000.0 μg/L), low LOD (4.0 μg/L), nice accuracy (recovery of 93.7–109.6 %) and good selectivity. Finally, this method was applied to visual detection of As(V) in rice samples with different varieties.